The Impact of Information Technology Innovation in Human Resource Management in The Digital Era Using The Ishikawa Method Case Study at PT Semanggi 3 - Siti Fatimatus Zahro; Pribadiyono Pribadiyono (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Rapid digital transformation requires companies to strengthen human resource management (HRM) governance by effectively leveraging information technology. However, gaps often occur between the expected benefits of digital systems and their actual implementation, particularly in infrastructure readiness, employee capability, and organizational acceptance. This study aims to examine the impact of information technology innovation on HRM governance and to identify key factors influencing the success and constraints of HRIS implementation at PT. Semanggi 3. The research employs a qualitative descriptive approach using the Ishikawa (fishbone diagram) analysis to identify root causes affecting technology adoption. The analysis categorizes influencing factors into six major variables: Man, Method, Material, Machine, Environment, and Management. The findings indicate that HRIS implementation generally performs well, with the Customer Satisfaction Index (CSI) showing “Excellent” and “Very Good” ratings across most service aspects. Nevertheless, several gaps remain, particularly in infrastructure readiness, technical training, and employee adaptability to digital transformation. Strengthening digital competencies, improving IT infrastructure, and ensuring continuous managerial support are identified as essential strategies for optimizing technology utilization in HRM governance.